2020
DOI: 10.1089/whr.2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

Is Periconceptional Substance Use Associated with Unintended Pregnancy?

Abstract: Background: To evaluate the relationship between periconceptional (period before and/or after conception) substance use and unfavorable pregnancy contexts, including unintended pregnancy. Materials and Methods: This is a cross-sectional analysis of English-or Spanish-speaking women aged 16-44 years with pregnancies <24 weeks' gestation presenting to pregnancy testing clinics and enrolled between June 2014 and June 2015. Participants self-reported periconceptional substance use (tobacco, alcohol, marijuana, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the same vein, a self-reported periconceptional substance use study conducted among women reported that women who use alcohol were more likely to report unintended pregnancy. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, a self-reported periconceptional substance use study conducted among women reported that women who use alcohol were more likely to report unintended pregnancy. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Only 2 prior studies measured ambivalent pregnancy intention in studying preconception behavior. Lundsberg et al 7 found that in a sample of healthy pregnant women, ambivalence toward a current pregnancy was associated with greater preconception alcohol intake and smoking. In contrast, the 2004 Behavior Risk Factor Surveillance System data showed no association between ambivalent intention and smoking or alcohol intake 32 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Healthy preconception behaviors such as engaging in physical activity (PA) at recommended guidelines can be protective against excessive weight gain and gestational diabetes, whereas risky behaviors such as smoking and high alcohol consumption are associated with reduced fertility, a higher likelihood of unintended pregnancies, and adverse neonatal outcomes. [6][7][8][9] AYA survivors are less physically active, have higher rates of smoking, and drink alcohol at similar rates in comparison with peers without cancer. 10,11 Poor health behaviors in AYA survivors are concerning because they may adversely affect already increased reproductive risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with substance use have reported a higher prevalence of unintended pregnancies. However, these studies have been limited to small-scale and hospital-based investigations 12,13 . To address this gap, this study investigates the association of preconception substance use to unintended pregnancy and its sub-types, that is, mistimed, unwanted, and ambivalent, using large national data from the Pregnancy Risk Assessment Monitoring System (PRAMS).…”
mentioning
confidence: 99%